An endocrine-disrupting agricultural contaminant impacts sequential female mate choice in fish. (June 2018) - Tomkins, Patrick; Saaristo, Minna; Bertram, Michael G.; Michelangeli, Marcus; Tomkins, Raymond B.; Wong, Bob B.M.
Abstract: The environmental impact of endocrine-disrupting chemicals (EDCs)—compounds that interfere with endocrine system function at minute concentrations—is now well established. In recent years, concern has been mounting over a group of endocrine disruptors known as hormonal growth promotants (HGPs), which are natural and synthetic chemicals used to promote growth in livestock by targeting the endocrine system. One of the most potent compounds to enter the environment as a result of HGP use is 17β-trenbolone, which has repeatedly been detected in aquatic habitats. Although recent research has revealed that 17β-trenbolone can interfere with mechanisms of sexual selection, its potential to impact sequential female mate choice remains unknown, as is true for all EDCs. To address this, we exposed female guppies ( Poecilia reticulata ) to 17β-trenbolone at an environmentally relevant level (average measured concentration: 2 ng/L) for 21 days using a flow-through system. We then compared the response of unexposed and exposed females to sequentially presented stimulus (i.e., unexposed) males that varied in their relative body area of orange pigmentation, as female guppies have a known preference for orange colouration in males. We found that, regardless of male orange pigmentation, both unexposed and exposed females associated with males indiscriminately during their first male encounter. However, during the second male presentation, unexposed females significantly reduced the amount of time they spent associating with low-orange males if they had previously encountered a high-orange male. Conversely, 17β-trenbolone-exposed females associated with males indiscriminately (i.e., regardless of orange colouration) during both their first and second male encounter, and, overall, associated with males significantly less than did unexposed females during both presentations. This is the first study to demonstrate altered sequential female mate choice resulting from exposure to an endocrine disruptor, highlighting the need for a greater understanding of how EDCs may impact complex mechanisms of sexual selection. Graphical abstract: Image 1 Highlights: 17β-trenbolone (TB) is a widespread agricultural contaminant used in cattle farming . Female guppies were exposed to TB at an environmentally relevant level for 21 days. TB altered sequential female mate choice in guppies. Females exposed to TB associated with males less overall than unexposed females. First study to show disruption of sequential female mate choice by exposure to an endocrine disruptor.